Task Scheduling and Resource Optimization in Cloud Computing Using Deadline-Aware Particle Swarm Technique: A Review - Shruti,; Sharma, Meenakshi (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is defined as that type of computing that relies on sharing computing resources rather than having local servers or personal devices to handle applications. Cloud computing is used to achieve coherence and economy of scale over a network. Basically, cloud computing is a general term for the delivery of hosted services over the internet. Various characteristics which comes under cloud computing includes its location independent, multi-tenancy, its reliability and security, and its on-demand self service etc. Cloud Computing is spreading through IT world with innovative start-ups. Companies in the financial sector are also adopting cloud computing for specific workloads. Various strategies are used for optimization in cloud computing in which particle swarm optimization is one of them. It is used to achieve task scheduling algorithm. To achieve better results and performance, we used Particle Swarm Optimization.